The Role of Green Financial Literacy, Sustainable Awareness, Green Banking Products, and Regulatory Support in Shaping Consumer Adoption of Sustainable Finance Services - Helda Marlin Ala; Nitaniel Hendrik; Mesri Welhelmina Nisriani Manafe (Malaqbi Publisher, 2026)
This study investigates the role of green financial literacy, sustainable awareness, green banking products, and regulatory support in shaping consumer adoption of sustainable finance services. With increasing global emphasis on environmental sustainability, understanding the factors influencing consumer engagement with green financial products is essential for promoting responsible financial behavior. Using a quantitative approach, data were collected from 250 consumers via structured questionnaires and analyzed using Structural Equation Modeling (SEM). The results indicate that all four factors significantly and positively influence adoption behavior, with green financial literacy having the strongest effect, followed by sustainable awareness, green banking products, and regulatory support. These findings highlight the need for a holistic strategy that integrates knowledge enhancement, awareness programs, accessible product offerings, and robust regulatory frameworks to foster sustainable financial practices. The study provides theoretical contributions by linking financial literacy, environmental awareness, product innovation, and institutional support to adoption behavior, and practical implications for policymakers, financial institutions, and educators in advancing sustainable finance markets.